ANTICONVULSANT PROPERTY OF SYNTHESIZED COMPOUND DHPM-5 IN LABORATORY ANIMALS - UPADHYAY, PRABHAT; KUMAR YADAV, ASHUTOSH; PANJWANI, DHARAMVEER; SACHAN, NARSINGH (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present study was undertaken to investigate the anti-convulsant effects of dihydropyrimidinone-5 (DHPM-5) in animal models. Materials and Methods: Swiss albino mice were used for the study. The test drug and standard drugs were administered once daily for a period of 14 days. Maximal electroshock (MES) induced convulsion and strychnine induced convulsion models were used for the study. Phenytoin (PHT) and Diazepam were used as standard agents throughout the study. Results and Discussion: Anti-convulsant studies with test drug showed a significant protection in MES induced convulsion models in a dosedependent manner. There was a significant (p<0.05) decrease in the duration of tonic hind limb extension at both the doses of test drug (200 mg/kg) in MES model. Compared with the control group, treatment with test drug had no significant effect on onset and duration of convulsions in the strychnine induced seizure model. As expected, the animals treated with diazepam 4 mg/kg increased onset, duration of convulsions and latency to death as compared with control group. In all groups, all animals had seizures and all died. DHPM-5 has an influence on the excitatory and inhibitory neurotransmission, of special interest being the increase in the gamma amino butyric acid levels. Conclusion: The presence of the chemical constituents gave strength to its anti-convulsant action. However, further research is warranted to determine the specific mode of its anti-convulsant activity. Keywords: Dihydropyrimidinone-5, Strychnine, Seizure, Neurotoxicity.